2012
DOI: 10.1111/j.1600-0722.2012.01002.x
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial–mesenchymal interactions induce enamel matrix proteins and proteases in the epithelial cells of the rests of Malassez in vitro

Abstract: Epithelial-mesenchymal interactions influence morphogenesis and cell differentiation in periodontal tissue regeneration. The current study examined the expression of amelogenin, ameloblastin, matrix metallopeptidase-20 (MMP-20), and kallikrein-4 (KLK-4) and their effects on the interactions between the epithelial cells of Malassez and periodontal ligament fibroblasts. Explants of human periodontal ligament tissues produced outgrowths containing both the epithelial cells of Malassez and periodontal ligament fib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 49 publications
(85 reference statements)
1
10
0
1
Order By: Relevance
“…Cells were used as confluent monolayers for experiments at subculture levels 2–5. We confirmed that these were epithelial cells, without contamination with fibroblasts, by staining with an epithelial cell‐specific marker, cytokeratin, as we have reported previously . All tissue culture reagents were from Invitrogen/Gibco BRL (Carlsbad, CA, USA), if not otherwise indicated.…”
Section: Methodssupporting
confidence: 84%
See 1 more Smart Citation
“…Cells were used as confluent monolayers for experiments at subculture levels 2–5. We confirmed that these were epithelial cells, without contamination with fibroblasts, by staining with an epithelial cell‐specific marker, cytokeratin, as we have reported previously . All tissue culture reagents were from Invitrogen/Gibco BRL (Carlsbad, CA, USA), if not otherwise indicated.…”
Section: Methodssupporting
confidence: 84%
“…Cells were used as confluent monolayers for experiments at subculture levels 3–10. For epithelial rest cells of Malassez , the tissue fragments were cultured in the epithelial medium described above for human gingival epithelial cells. Cells were used as confluent monolayers for experiments at subculture levels 2–5.…”
Section: Methodsmentioning
confidence: 99%
“…72 When ERM cells are cocultured with PDL fibroblasts, protein expression of both cell types is different compared to the proteins expressed by each cell type cultured individually. [73][74][75][76] Such in vitro experiments have helped to elucidate the potential interactions between ERM cells and PDL fibroblasts that are found in close proximity in vivo. In one experiment, porcine ERM cells were cocultured with porcine PDL fibroblasts in special plates designed to physically separate the 2 cell types by a microporous membrane.…”
Section: Epithelial Cell Rests Of Malassez and Homeostasis Of The Pdlmentioning
confidence: 99%
“…AMBN is functional, and is also expressed in adult bone repair (Nakamura et al, 2006; Spahr et al, 2006; Tamburstuen et al, 2010). During tooth development AMBN is induced by epithelial-mesenchymal interactions and expressed in MSC and epithelial cells (Fong et al, 1998; Takahashi et al, 2012) and in the pre-secretory and secretory stages of ameloblasts development (Nanci et al, 1998). Exon 5 and exon 6 knock down experiments in mice did however, not have any observable effects on the pre-secretory stages of ameloblasts development (Wazen et al, 2009).…”
Section: Discussionmentioning
confidence: 99%